FGF-2 addition during expansion of human bone marrow-derived stromal cells alters MSC surface marker distribution and chondrogenic differentiation potential - Hagmann, Sébastien; Moradi, Babak; Frank, Sebastian; Dreher, Thomas; Richter, Wiltrud; Gotterbarm, Tobias (Cell proliferation, 2013)
Objectives Although clinical applications using mesenchymal stromal cells (MSCs) are becoming more frequent, procedures for their in vitro culture are far from standardized. Growth factors such as FGF-2 are frequently added during expansion to improve population growth and differentiation characteristics. However, up to now its influence on surface marker distribution of MSCs has been close to unknown. The purpose of this study was therefore to analyse effects of FGF-2 supplementation on pre-selection of MSC subpopulations. Materials and methods Mesenchymal stromal cells were harvested from bone marrow of six patients and expanded in alpha-MEM or DMEM-LG. Starting in passage 2, 10 ng/ml FGF-2 was administered and non-supplemented media were used as controls. Growth indices were calculated from P0 to P4. After P4, fluorescence cytometry for common MSC surface markers was performed and standard chondrogenic, adipogenic and osteogenic differentiation protocols were applied. Results Cell population growth indices were higher for those in FGF-2 supplemented media. Significant differences in surface marker distribution were observed for CD13, CD14, CD49, CD90, CD340 and STRO-1 depending on respective culture conditions. FGF-2 suppressed CD146 expression in both alpha-MEM and DMEM-LG. No differences in adipogenic and osteogenic differentiation potential could be observed, while FGF-2 significantly improved chondrogenic differentiation in DMEM-LG. Conclusions While holding the benefit of improving MSC chondrogenic differentiation potential, FGF-2 pre-selects certain MSC subtypes. Our data clearly show that expansion culture conditions have a significant effect on distribution of a number of MSC surface markers.
Gesehen am 15.10.2021